2006
DOI: 10.1186/1475-2891-5-26
|View full text |Cite
|
Sign up to set email alerts
|

Low carbohydrate diets in family practice: what can we learn from an internet-based support group

Abstract: The Active Low-Carber Forums (ALCF) is an on-line support group started in 2000 which currently has more than 86,000 members. Data collected from posts to the forum and from an online survey were used to determine the behavior and attitudes of people on low carbohydrate diets. Members were asked to complete a voluntary 27-item questionnaire over the internet. Our major findings are as follows: survey respondents, like the membership at large, were mostly women and mostly significantly overweight, a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 38 publications
(26 reference statements)
1
38
1
Order By: Relevance
“…75 A survey of more than 2000 members of an online, lowcarbohydrate support group found positive health outcomes for participants, such as decreased body weight and an improved lipid profile. 76 A survey of more than 2500 people following a low-carbohydrate diet of some type (or a paleo diet, which is often a reduced-carbohydrate diet) found a variety of positive health benefits such as reduced weight, hunger, irritable bowel syndrome symptoms, joint pain, arthritis pain, brain fog and acne, as well as improved glycaemic control, psychological well-being, athletic performance and energy. 77 About 100 people from the National Weight Control Registry, which tracks people who have long-term weight loss success, reported using a low-carbohydrate diet approach and reported long-term weight loss with reduced hunger.…”
Section: Aim and Objectivesmentioning
confidence: 99%
“…75 A survey of more than 2000 members of an online, lowcarbohydrate support group found positive health outcomes for participants, such as decreased body weight and an improved lipid profile. 76 A survey of more than 2500 people following a low-carbohydrate diet of some type (or a paleo diet, which is often a reduced-carbohydrate diet) found a variety of positive health benefits such as reduced weight, hunger, irritable bowel syndrome symptoms, joint pain, arthritis pain, brain fog and acne, as well as improved glycaemic control, psychological well-being, athletic performance and energy. 77 About 100 people from the National Weight Control Registry, which tracks people who have long-term weight loss success, reported using a low-carbohydrate diet approach and reported long-term weight loss with reduced hunger.…”
Section: Aim and Objectivesmentioning
confidence: 99%
“…For example, increase in carbohydrate consumption was found to be associated with increased weight. [2][3][4] On the other hand, increased consumption of vegetables and fruit was associated with weight reduction efforts. 5,6 High protein diet was promoted as a weight reduction diet regime because protein was found to induce sustained reduction in appetite.…”
Section: Introductionmentioning
confidence: 99%
“…Until we reach agreement on the recommended definitions and conditions, we recognize that "fad" diet is a term meant to disparage people from trying a dietary strategy that, in the case of low-carbohydrate diets is, in fact, not unconventional [27] or recent [18]. Although low-carbohydrate diets have always been considered one alternative, recent results and the underlying physiology suggest that it should be the default diet, the one to try first.…”
Section: In the Meantime: The Default Diet For Diabetesmentioning
confidence: 94%
“…However, because the diet was hypocaloric, in absolute terms, this represented a switch from 97.0 (± 35.2) g/d to only 100.2 (± 37.9) g/d. In terms of food consumed, a poll of the Active Low-Carber Forums (http://forum.lowcarber.org/), an online support group, found that the major change was increased consumption of vegetables and leafy greens and not large increases in the meat or fat as popularly portrayed [27].…”
Section: Definitionsmentioning
confidence: 98%
See 1 more Smart Citation